تفسیرِ قرآن میں آثار صحابہ سے استدلال: قرطبی کی تفسیر سورہ البقرہ کا مطالعہ: Argument from the Sayings of the Companions in Qur’ānic Exegesis: A Study of Tafsīr Surah al-Baqarah by al-Qurtubī (Al-Qamar, 2019)
The present paper studies the argument from the sayings of the companions of the Prophet (ﷺ) in Qur’ānic exegesis in the light of Tafsīr Surah al-Baqarah by al-Qurtubī (1214-1273), a renowned Andalusian Islamic scholar and jurist. It finds that al-Qurtubī argues with the sayings of the Companions in various discussions related to Qur’ānic exegesis. According to the points mentioned with reference to Surah al-Baqarah, al-Qurtubī has explained various unfamiliar Qur’ānic words, the scenario of the revelation of different verses, the rules related to worship, the correct pronunciation of different Qur’ānic words and has resolved different variant readings of the Quran, etc. He has argued from the sayings of the Companions and has made a successful attempt to clarify the correct Islamic position in the relevant issues. This discussion also proves that among the verses whose interpretation is not known from Quran and Ḥadīth, the utmost importance should be given to the sayings of the Companions. If the Companions agree on the interpretation of a verse, then the commentators must adopt it, and it is not permissible to adopt the contrary. However, if there is a difference of opinion among the Companions in the relevant issue, then the opinion of those who are closer to Islamic point of view can be adopted
Keywords: Al-Qurtubī; Tafsīr; al-Baqarah; Companions; sayings